Effect of antenna frequency bands on the resolution of GPR images - Yochanang, Kiattisak; Boonpoonga, Akkarat; Akkaraekthalin, Prayoot; Bannawat, Lakkhana; Phongcharoenpanich, Chuwong (My University, 2017)
This paper presents an investigation of the effect of the antenna frequency band on the ground penetrating radar (GPR) image resolution. The investigation is achieved through simulations. In the simulations, two Scutcheon antennas are modeled as the receiving and transmitting antennas. A cross-shaped object is buried under the ground constructed with the dielectric material. The Gaussian pulses with different frequency bands is transmitted and propagated to the buried object. The EM wave scattered from the object is collected to form the GPR image. The simulation results obtained from different frequency band show that the resolution of the GPR image obtained from the wider frequency band is better than that of the GPR image obtained from narrower one.
Keywords: frequency band; ground penetrating radar image; resolution